Robust Hydrogel Adhesion by Harnessing Bioinspired Interfacial Mineralization. Issue 31 (8th July 2022) - Zhang, Jun; Wang, Yaya; Zhang, Jiajun; Lei, Iek Man; Chen, Guangda; Xue, Yu; Liang, Xiangyu; Wang, Daozeng; Wang, Guigen; He, Sisi; Liu, Ji
Abstract: Hydrogels have gained intensive interest in biomedical and flexible electronics, and adhesion of hydrogels to substrates or devices is indispensable in these application scenarios. Although numerous hydrogel adhesion strategies have been developed, it is still challenging to achieve a hydrogel with robust adhesion interface through a universal yet simple method. Here, a strategy for establishing strong interfacial adhesion between various hydrogels and a wide variety of substrates (i.e., soft hydrogels and rigid solids, including glass, aluminum, PET, nylon and PDMS) even under wet conditions, is reported. This strong interfacial adhesion is realized by constructing a bioinspired mineralized transition layer through ion diffusion and subsequent mineral deposition. This strategy is not only generally applicable to a broad range of substrates and ionic pairs, but also compatible with various fabrication approaches without compromising their interfacial robustnesses. This strategy is further demonstrated in the application of single‐electrode triboelectric nanogenerators (TENG), where a robust interface between the hydrogel and elastomer layers is enabled to ensure a reliable signal generation and output. Abstract : Robust hydrogel adhesion is achieved by constructing a bioinspired mineralized transition layer through ion diffusion and subsequent mineral deposition.